Systems Biology Approaches for Therapeutics Development Against COVID-19 - Jaiswal, Shweta; Kumar, Mohit; Mandeep,; Sunita,; Singh, Yogendra; Shukla, Pratyoosh (Frontiers in Cellular and Infection Microbiology, 2020)
Understanding the systems biology approaches for promoting the development of new therapeutic drugs is attaining importance nowadays. The threat of COVID-19 outbreak needs to be vanished for global welfare, and every section of research is focusing on it. There is an opportunity for finding new, quick, and accurate tools for developing treatment options, including the vaccine against COVID-19. The review at this moment covers various aspects of pathogenesis and host factors for exploring the virus target and developing suitable therapeutic solutions through systems biology tools. Furthermore, this review also covers the extensive details of multiomics tools i.e., transcriptomics, proteomics, genomics, lipidomics, immunomics, and in silico computational modeling aiming towards the study of host–virus interactions in search of therapeutic targets against the COVID-19.